let k be Nat; :: thesis: for seq being ExtREAL_sequence st seq is convergent_to_finite_number holds
( seq ^\ k is convergent_to_finite_number & seq ^\ k is convergent & lim seq = lim (seq ^\ k) )

let seq be ExtREAL_sequence; :: thesis: ( seq is convergent_to_finite_number implies ( seq ^\ k is convergent_to_finite_number & seq ^\ k is convergent & lim seq = lim (seq ^\ k) ) )
set seq0 = seq ^\ k;
assume A1: seq is convergent_to_finite_number ; :: thesis: ( seq ^\ k is convergent_to_finite_number & seq ^\ k is convergent & lim seq = lim (seq ^\ k) )
then A2: ( not lim seq = +infty or not seq is convergent_to_+infty ) by MESFUNC5:50;
A3: ( not lim seq = -infty or not seq is convergent_to_-infty ) by ;
seq is convergent by ;
then A4: ex g being Real st
( lim seq = g & ( for p being Real st 0 < p holds
ex n being Nat st
for m being Nat st n <= m holds
|.((seq . m) - (lim seq)).| < p ) & seq is convergent_to_finite_number ) by ;
then consider g being Real such that
A5: lim seq = g ;
A6: for p being Real st 0 < p holds
ex n being Nat st
for m being Nat st n <= m holds
|.(((seq ^\ k) . m) - (lim seq)).| < p
proof
let p be Real; :: thesis: ( 0 < p implies ex n being Nat st
for m being Nat st n <= m holds
|.(((seq ^\ k) . m) - (lim seq)).| < p )

assume 0 < p ; :: thesis: ex n being Nat st
for m being Nat st n <= m holds
|.(((seq ^\ k) . m) - (lim seq)).| < p

then consider n being Nat such that
A7: for m being Nat st n <= m holds
|.((seq . m) - (lim seq)).| < p by A4;
take n ; :: thesis: for m being Nat st n <= m holds
|.(((seq ^\ k) . m) - (lim seq)).| < p

hereby :: thesis: verum
let m be Nat; :: thesis: ( n <= m implies |.(((seq ^\ k) . m) - (lim seq)).| < p )
assume A8: n <= m ; :: thesis: |.(((seq ^\ k) . m) - (lim seq)).| < p
m <= m + k by NAT_1:11;
then n <= m + k by ;
then |.((seq . (m + k)) - (lim seq)).| < p by A7;
hence |.(((seq ^\ k) . m) - (lim seq)).| < p by NAT_1:def 3; :: thesis: verum
end;
end;
lim seq = g by A5;
hence A9: seq ^\ k is convergent_to_finite_number by ; :: thesis: ( seq ^\ k is convergent & lim seq = lim (seq ^\ k) )
hence seq ^\ k is convergent by MESFUNC5:def 11; :: thesis: lim seq = lim (seq ^\ k)
hence lim seq = lim (seq ^\ k) by ; :: thesis: verum